Studi Penggunaan Dan Penerapan Sistem Elektronik Retribusi Terhadap Pemakai Jasa Terminal - Irfan Zakiy Mubaroh; Deddy Nurdin; Aang Gunawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this research is to identify and analyse the strengths, weaknesses, opportunities, and threats of specific information system regarding online electronic retribution. Post positivistic qualitative method or qualitative method or interpretive method was used to analyse the data. The population in this research were employees of Transportation Department of Road Terminal Management unit. The sample was the head of operational and road transportation terminal management unit. The data was collected through observation, interview, and literature. SWOT method was used to analyse the data. The result shows that agency’s position is in quadrant I with the condition of SO (Strength – Opportunity) in the e- retribution system with coordinate (0.75;0.40).